Study of the Effect of Grouting Material Strength on Semiflexible Pavement Material - Qingguo Yang; Ying Li; Hua Zou; Long Feng; Nan Ru; Lin Gan; Jiyun Zhang; Jiansong Liu; Chengyang Wang (Advances in Materials Science and Engineering)
In this study, cement mortars with different strengths are poured into the large void matrix asphalt macadam material as a semiflexible pavement (SFP) material and the experimental research is carried out. The current research on SFP is mainly focused on the performance of grouting materials and the influence of grouting matrix materials on the overall mechanical properties of SFP and road performance. However, there are some flaws in the study of the influence of grouting material strength on the performance of SFP materials: the difference between the strengths of the selected grouting materials is relatively small, and in some studies, the chosen grouting material strength is low, which leads to insignificant improvements of SFP material performance; besides, the research indicators are also not very comprehensive. In this study, cement grouting asphalt macadam materials are selected as the research object to examine the effect of grouting material strength on the mechanical properties and road performance of SFP materials. Grouting materials with strengths of 19.8 MPa, 30.7 MPa, and 40.2 MPa were poured into the matrix asphalt macadam with a target void ratio of 24% and asphalt content of 2.9% to prepare the corresponding SFP test specimens. The SFP specimens were then subjected to the compressive test, flexural and tensile test, high-temperature stability test, and low-temperature crack resistance test, and the compressive resilient modulus was measured, thereby analyzing the effect of the cement slurry strength on the cement grouting asphalt macadam materials. The results show that when the strength of the cement mortar is 19.8 MPa, 30.7 MPa, and 40.2 MPa, the corresponding SFP material has better mechanical properties. When the strength of the grouting material is 40.2 MPa, the compressive strength of the SFP material is about the same as that of the grouting material. The strength is more than double that of 19.8 MPa and 30.7 MPa, and the flexural tensile strength and elastic modulus also have the above growth laws. The low-temperature crack resistance and high-temperature stability of the SFP material are enhanced with the increase in the strength of the grouting material. When the strength of the grouting material is 40.2 MPa, the mechanical properties and road performance of the SFP material are relatively better. This study provides a reference for strengthening the mechanical properties of SFP materials and boosting the crack resistance of SFP.